MODELING SUB-SURFACE FLOW OF WATER IN SLOPING FIELD - Patel, Neelam; Kar, S.; Rajput, T.B.S. (Journal of Soil and Water Conservation, 2022)
A conceptual deterministic numerical model has been utilized to predict the distribution of soil water pressure in a small (1.2 m x 1,0 m) two dimensional flow region which is bounded by a sloping surface at the top, an impervious plane at bottom, a vertical bound at the beginning of the down slope region where there is no flow and a stream at the lower vertical bound (Fig. 2). The equation (d/dx [K(F,w) do/dz] + d/dz [K(F, iv) aVaz] = C dwdtt) being a parabolic, which fonts a tri-diagonal system wizen finite difference, is solved by line successive over relaxation numerical technique after imposing necessary static and steady state initial conditions. Using initial (t=0) distribution of water pressure as estimated by Gauss-elimination technique and imposing transient boundary conditions, the flow equation is solved to get distribution of water pressure at different time during rainfall at a constant rate. The predicted water pressure data are finally utilized to estimate vertical and lateral flow of water in the flow region (Fig. 2). "The output of the model in terms of responses of soil water pressure to rainfall infiltration and sloping water-table position, decreasing trend of vertical flow of water with increasing soil depth and lateral distance as well as of increasing lateral flow in deeper layers at later time periods, show that this model is suitable to predict water pressure distribution in sloping fields.